The Legal Position of the Sale & Purchase Agreement between the Developer & the Purchaser for Land Objects That are Still in the Process of Splitting - Puji Haryanti; Bambang Tri Bawono (Sultan Agung Notary Law Review, 2022)
The purpose of this research is to find out and analyze the legal position of the binding sale and purchase agreement between the developer and the buyer for land objects that are still in the process of splitting and analyze the role of a notary in making a binding sale and purchase deed where the land object is still in the process of splitting. This type of research is sociological juridical. The research approach used is descriptive research. Source of data used primary data and secondary data. Collection data used literature study and field study. The data analysis technique uses an interactive analysis model. The results of the study show that the legal position of the binding agreement on the sale and purchase of land rights made by a notary is recognized as a valid agreement, the binding agreement on sale and purchase aims to bind the seller and the buyer as a preliminary agreement in order to prepare the main agreement/subject agreement which will be carried out later, in the case of this is the Deed of Sale and Purchase. The role of the Notary in making PPJB is as an official authorized to make authentic deeds, intermediary and recorder of the will of the parties in the buying and selling process and as a witness that a deed has been carried out.